Buried pipeline installation impacts on soil structure and crop root decomposition - Elnaz Ebrahimi; Mehari Z. Tekeste; Robert Horton; H. Mark Hanna (Agricultural & Environmental Letters, 2022)
Abstract The severe manipulation of soil that occurs in the right‐of‐way (ROW) easement areas for pipeline installation leads to soil degradation and yield loss. The objectives of this study were to investigate the use of the Visual Evaluation of Soil Structure method (VESS) and root litter sampling as alternative ways to characterize pipeline installation impacts on soil degradation. Digital images of aggregate specimens and root samples were obtained from disturbed (trenched and highly trafficked ROW areas) and undisturbed (adjacent to the ROW) soil profiles one month after maize (Zea mays L.) harvest in Iowa. Images of soil aggregates indicated that pipeline installation deteriorated soil structure. Root attributes were significantly (p < 0.05) affected by the ROW activities. The non‐decomposed root mass in the highly trafficked area (3,568 kg ha–1) was two times greater than the root mass in undisturbed soil (1,779 kg ha–1). These data provide evidence that soil structure quality and root decomposition rates are affected by soil disturbance. The VESS and root measurements can be used in future studies to evaluate the impacts of soil disturbance.